Long-term survival analysis of ultrasound-guided percutaneous microwave ablation for hepatocellular carcinoma conforming to the Milan criteria: primary versus recurrent HCC - Jing Zhang; Guanya Guo; Tao Li; Changcun Guo; Ying Han; Xinmin Zhou (International Journal of Hyperthermia)
Background This study compared long-term outcomes between patients with initial hepatocellular carcinoma (IHCC) and those with recurrent HCC (RHCC) treated with microwave ablation (MWA).Methods This retrospective study included 425 patients with HCCs (294 IHCCs and 131 RHCCs) within the Milan criteria who were treated with ultrasound-guided percutaneous MWA between January 2008 and November 2021. All patients with RHCC had previously undergone MWA for initial HCC. Overall survival (OS) and recurrence-free survival (RFS) rates were compared between the IHCC and RHCC groups before and after propensity score matching (PSM).Results Before matching, the 1-, 3-, 5-, and 10-year OS rates in the IHCC group were 95.9%, 78.5%, 60.2%, and 42.5%, respectively, which were significantly higher than those in the RHCC group (93.8%, 70.0%, 42.0%, and 6.6%, respectively). This difference remained significant after PSM. However, subgroup analyses suggested that there were no significant differences in OS rates between IHCC and RHCC in patients with solitary HCC ≤3.0 cm, AFP ≤200 ng/mL, ablative margins ≥0.5 cm, or Albumin-Bilirubin (ALBI) grade 1. RFS was significantly higher in IHCC than in RHCC before and after PSM, as well as in subgroup analyses. ALBI grade (hazard ratio (HR), 2.38; 95% CI: 1.46–3.86; p < 0.001), serum AFP level (HR, 2.07; 95% CI: 1.19–3.62; p = 0.010) and ablative margins (HR, 0.18; 95% CI: 0.06-0.59; p = 0.005) were independent prognostic factors for OS of RHCC. Serum AFP(HR, 1.29; 95% CI: 1.02–1.63, p = 0.036) level was the only factor associated with RFS in RHCC.Conclusions MWA yielded comparable OS in IHCC and RHCC patients with solitary HCC ≤3.0 cm, AFP ≤200 ng/mL, ablative margins ≥0.5 cm, or ALBI grade 1.